PENERAPAN MODEL CONCEPT SENTENCE UNTUK MENINGKATKAN KEMAMPUAN MENULIS KARANGAN NARASI SISWA KELAS IV SD - Rahmani, Annisa Nur (2016)
Penelitianinidilatarbelakangiolehkurangnyakemampuanmenuliskarangannarasisiswa, haltersebutdikarenakan guru menggunakanmetodeceramahdanlatihan, sehinggahasilbelajarpuntidakdapatmencapai target yang telahditentukan.Untukmengatasimasalahtersebut, penelitimenerapkan model concept sentence yang mampumeningkatkankemampuanmenuliskarangannarasisiswa.Penelitianinibertujuanmendeskripsikanpenerapan model concept sentence untukmeningkatkankemampuanmenuliskarangannarasisiswakelas IV SD S Bandung.PenelitianinidilaksanakandenganmenggunakanmetodepenelitiantindakankelasmenurutKemmisdanMc Taggart yang terdiriatastahapperencanaan, pelaksanaan, observasi, danrefleksi.Partisipandalampenelitianiniadalahsiswakelas IV SD S Bandung berjumlah 36 siswa, terdiridari 16 siswalaki-lakidan 20 siswaperempuan. Instrument penelitian yang digunakanadalahlembarobservasiaktivitas guru dansiswa, dantes.Pengumpulan data dilakukandenganteknikobservasi yang digunakanuntukmengumpulkandalatakualitatif, dantesuntuk data kuantitatif.Hasilobservasidiolahdenganreduksi data, penyajian data, danverifikasi data.Sedangkantesdiolahdenganmenghitungnilai rata-rata danpersentaseketuntasanbelajar.Kesimpulan yang diperolehdaripenelitianiniadalahpenerapan model pembelajaranconcept sentencemampumeningkatkankemampuanmenuliskarangannarasi. Hal initerlihatdaripeningkatanpersentasekemampuanmenuliskaranganarasisiswapadasiklus I sebesar 63,88%, kemudianmeningkatpadasiklus II menjadi 75,00%, danpadasiklus III sebesar 86,11%;-- The background of this research is the less ability of student in the writing the narration, the reasons of that, because the teacher use the talkative and exercise methods, therefore the study result of it cannot reach the target. Based on the problem below, the researcher applying the different method to increase the students ability of narration writing. The purposes of this research is describing of application the concept sentence model learning to increase the students ability of narration writing in fourth grade of S Bandung elementary school . this research use the classroom action research, according to Kemmis and Mc Taggart It's consist of planning, implementation, observation, and reflection. The participant of this research are the teacher and student in fourth grade of S Bandung elementary school, with total number of students 36, consist of 16 male students and 20 female students. The research instrument that had been use is the observation sheet of observation learning activity of the teacher and student. also used the test. Technique of collecting the Data is observation, which is used to collect the qualitative Data, beside that the researcher also used the test technique of the quantitative Data. The result of the observation is processing by the Reduction Data, Presentation Data, and Verification Data. Meanwhile the test result is processing by counting the average grade and the percentage of completeness learning. The conclusion of this research is applying the concept sentence model learning that can increase the student ability in narration writing. It had been enchanced of the percentage the student ability in narration writing in the first cycle is 63,88%, then increasing in the second cycle is 75,00%, Then, in the end of third cycle is 86,11%.